A food resilience model integrating local wisdom and sociotechnical dynamic systems: Case study flood-affected communities in the Bengawan solo area - Issa Dyah Utami; Nachnul Anshori; Haryani Saptaningtyas; Septin Puji Astuti (Progress in Disaster Science)
This study aimed to identify local potential and design a food resilience model based on local wisdom regarding floods. Floods can degrade the quality of food products. Indonesian people are known to have local wisdom on maintaining food resilience to mitigate natural disasters. This study proposes improving community preparedness for disaster threats and strengthening their capacity to respond effectively by integrating local wisdom, thereby improving food resilience and achieving disaster mitigation. To support research exploring how local wisdom can be effectively integrated into food resilience in communities affected by natural disasters, especially floods, effective strategies and methods are required to combine local wisdom with scientific and technological approaches. The sociotechnical system method and dynamic system approach were used to develop a model that can provide information to the community and government, thereby optimizing the function of local wisdom in food resilience. This study shows that local wisdom is important for flood mitigation and food resilience in communities affected by flood disasters. Based on the simulation results, the best scenario was obtained for the three regions. Governments can use these proposals to formulate policy priorities for implementation in each region.